2009
DOI: 10.1002/em.20518
|View full text |Cite
|
Sign up to set email alerts
|

Differential mutagenicity of aflatoxin B1 in the liver of neonatal and adult mice

Abstract: Children are generally more sensitive to toxicants than adults, including an increased sensitivity to genotoxic carcinogens. We previously demonstrated that neonatal mice are also more sensitive to the mutagenic effects of the direct alkylating agents N-ethyl-N-nitrosoamine and the arylamine 4-aminobiphenyl than adult mice. In this study, we have evaluated the effect of age on the mutagenicity of the fungal toxin and liver carcinogen aflatoxin B(1) (AFB(1)). Neonatal Big Blue transgenic mice were treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
2
11
0
9
Order By: Relevance
“…Earlier analyses showed a 13-to 15-fold increase in the MF of the gpt transgene at 3 weeks after treatment of 4-day-old mice (Woo et al, 2011); our present findings show that the MF continued to increase up to 20-fold over DMSO-treated controls at 10 weeks thereafter. These results are in agreement with another study that found a 22-fold increase in base substitution and frameshift mutations in the cII transgene of neonatal Big Blue B6C3F1 mice 6 weeks after treatment with AFB 1 (Chen et al, 2010). The slower increase in MF in the liver from 3 to 10 weeks was very likely due to the decrease in growth rate of the liver after 3 weeks.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Earlier analyses showed a 13-to 15-fold increase in the MF of the gpt transgene at 3 weeks after treatment of 4-day-old mice (Woo et al, 2011); our present findings show that the MF continued to increase up to 20-fold over DMSO-treated controls at 10 weeks thereafter. These results are in agreement with another study that found a 22-fold increase in base substitution and frameshift mutations in the cII transgene of neonatal Big Blue B6C3F1 mice 6 weeks after treatment with AFB 1 (Chen et al, 2010). The slower increase in MF in the liver from 3 to 10 weeks was very likely due to the decrease in growth rate of the liver after 3 weeks.…”
Section: Discussionsupporting
confidence: 93%
“…a Because few mutants were available for analysis, data from male and female mice were combined. bacterial reporter genes in transgenic mice established that neonatal exposure to AFB 1 leads to a 20-fold increase in the frequency of point mutations in the gpt gene in the liver (Chen et al, 2010;Woo et al, 2011). In the present investigation, we studied the ability of AFB 1 to induce mutations in the gam and red genes of a λEG10 reporter in mouse liver.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Sendo assim, é essencial direcionar corretamente a equipe e saber trabalhar bem todos os imprevistos que possam vir a ocorrer durante o percurso. (Joslin & Müller, 2015) Para medir a eficiência do projeto por meio de diferentes pontos de vista (Shenhar, Dvir, Levy, & Maltz, 2001) Gráfico 1 -Sucesso do projeto quanto ao prazo Fonte: Adaptada de (Shenhar et al, 2001) A pressão para que os negócios incorporem os princípios do desenvolvimento sustentável vem aumentando dentre as políticas e atividades da empresa. O gerenciamento de gerenciamento de projetos não é diferente, cada vez mais a forma como são praticados devem se alinhar a esse conceito exigido pelos stakeholders.…”
Section: Eficiência Em Gerenciamento De Projetosunclassified
“…Several groups have recently determined mutational spectra induced by AFB 1 in bacterial reporter genes in transgenic B6C3F1 mouse liver [Chen et al 2010; Woo et al 2011]. …”
Section: Introductionmentioning
confidence: 99%